Comparison of IB-NOSA and Discovery Learning Models on Students' Scientific Literacy and Scientific Argumentation Skills in High School - Nur Rezki Octavia; Rachmawaty Rachmawaty; Oslan Jumadi; Firdaus Daud; Hartono Hartono; Nur Rezki Octavia; Rachmawaty Rachmawaty; Oslan Jumadi; Firdaus Daud (Universitas Negeri Malang, 2026)
This study aimed to describe and compare the effects of the IB-NOSA and Discovery Learning models on scientific literacy and scientific argumentation skills of tenth-grade high school students, as well as to examine the significant differences between the two models in the context of Biology learning. This study was quasi-experimental research with a pretest–posttest nonequivalent control group design. The study involved two classes, namely Experimental Class I which was taught using the IB-NOSA model and Experimental Class II which was taught using the Discovery Learning model. The research sample consisted of 72 students of grade 10, with 36 students in Experimental Class I and 36 students in Experimental Class II. Data were collected using a scientific literacy test based on contextual stimuli and a scientific argumentation test in the form of essay questions assessed using the Toulmin Argumentation Pattern rubric. Before hypothesis testing, the data were analyzed using normality and homogeneity tests as prerequisite tests. Hypothesis testing was conducted using Analysis of Covariance (ANCOVA). The results showed that the Sig. value was 0.131 (p > 0.05), indicating that H₀ was accepted for the scientific literacy test, and the Sig. value was 0.004 (p < 0.05), indicating that H₀ was rejected. Thus, it can be concluded that the IB-NOSA and Discovery Learning models have a relatively similar effect on scientific literacy, but the IB-NOSA model is more effective in improving students’ scientific argumentation skills.